(untitled) (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2026)
The article publishes new data on the original type of cultural heritage of the Republic of Kazakhstan - rock art of the early Iron Age from the territory of Eastern Zhetysu. The collection includes petroglyphs of the early Saka period, late Saka and Hunno-Sarmatian times. These are images of predators, herbivores, anthropomorphic figures and household items made in the technique of piquetage and engraving. According to the manner of execution, there are ornamented, contour, silhouette images. The monuments indicate that nomadic groups living in the lowlands of the Zhetysu Alatau in the early Iron Age had original artistic images, which, nevertheless, are part of the core of the Scythian-Siberian animal style. The petroglyphs find analogies in the art of related nomads from other regions of Zhetysu and Southern Kazakhstan, as well as tribes that settled from Ordos to the Northern Black Sea region in the middle – end of the 1st millennium BC. Many individual images were lost due to natural and climatic factors, some are under threat of destruction.